Evaluation of the novel HEalthy Lifestyle Project (HELP) youth mental health e-intervention for lifestyle behaviour change and mental healthcare system impact: A randomized controlled trial protocol - Ria Patel; Patricia E. Longmuir; Marjorie Robb; Natasha Baechler; Kimberly Courtney; Mark Norris; Gary Goldfield; Fiona Cooligan; Shannon Watson; Paula Cloutier; Clare Gray (PLoS ONE, 2025)
Background Youth mental health is in crisis: suicide and self-harm doubled from 2019–2022; youth wait 8–12 months for care; 75% of youth with mental illness do not get care. Sleep, physical activity, and screen time impact mental wellbeing; lifestyle factors addressed with 95% of youth receiving mental health care. The virtual, asynchronous HELP (HEalthy Lifestyle Project) resource could enable step-by-step lifestyle behaviour change with or without professional support. HELP was collaboratively developed with youth experiencing mental distress, parents, and clinicians. Methods Youth 12–17 seeking mental health services will be randomized to receive six months of immediate HELP e-resource access or a waitlist control (ClinicalTrials.gov, #NCT06232733). The primary outcome is emotional health (Strength and Difficulties Questionnaire total score). Secondary outcomes include behaviour change readiness, sleep, physical activity, screen time, and quality of life. All outcomes will be assessed at 0, 3, 6, and 12 months. Healthcare system utilization, extracted from health records at 18 months, will be compared relative to intervention access and compliance between participants and matched controls. Discussion The HELP e-resource offers an accessible, stigma-free option for lifestyle support that could be widely available to youth experiencing mental distress. Healthy lifestyle behaviour change is a low-risk intervention that youth can access independently, or with support, whenever they are ready to engage, without waiting for specialist services. Healthy lifestyle behaviour change can enhance mental well-being and readiness to engage in treatment. Such changes could reduce the need for specialist support, alleviating an overburdened youth mental healthcare system.